PEGylated-thymoquinone-nanoparticle mediated retardation of breast cancer cell migration by deregulation of cytoskeletal actin polymerization through miR-34a. (May 2015) - Bhattacharya, Saurav; Ahir, Manisha; Patra, Prasun; Mukherjee, Sudeshna; Ghosh, Swatilekha; Mazumdar, Minakshi; Chattopadhyay, Sreya; Das, Tanya; Chattopadhyay, Dhrubajyoti; Adhikary, Arghya
Abstract: Thymoquinone (TQ), a major active constituent of black seeds of Nigella sativa, has potential medical applications including spectrum of therapeutic properties against different cancers. However, little is known about their effect on breast cancer cell migration, which is the cause of over 90% of deaths worldwide. Herein, we have synthesized TQ-encapsulated nanoparticles using biodegradable, hydrophilic polymers like polyvinylpyrrolidone (PVP) and polyethyleneglycol (PEG) to overcome TQ's poor aqueous solubility, thermal and light sensitivity as well as consequently, minimal systemic bioavailability which can greatly improve the cancer treatment efficiency. Sizes of synthesized TQ-Nps were found to be below 50 nm and they were mostly spherical in shape with smooth surface texture. Estimation of the zeta potential also revealed that all the three TQ-Nps were negatively charged which also facilitated their cellular uptake. In the present investigation, we provide direct evidence that TQ-Nps showed more efficiency in killing cancer cells as well as proved to be less toxic to normal cells at a significantly lower dose than TQ. Interestingly, evaluation of the anti-migratory effect of the TQ-Nps, revealed that PEG4000 -TQ-Nps showed much potent anti-migratory properties than the other types. Further studies indicated that PEG4000 -TQ-Nps could significantly increase the expression of miR-34a through p53. Moreover, NPs mediated miR-34a up-regulation directly down-regulated Rac1 expression followed by actin depolymerisation thereby disrupting the actin cytoskeleton which leads to significant reduction in the lamellipodia and filopodia formation on cell surfaces thus retarding cell migration. Considering the biodegradability, non-toxicity and effectivity of PEG4000 -TQ-Nps against cancer cell migration, TQ-Nps may provide new insights into specific therapeutic approach for cancer treatment.